2011
DOI: 10.1007/s13238-011-1088-0
|View full text |Cite
|
Sign up to set email alerts
|

The network of cytokines, receptors and transcription factors governing the development of dendritic cell subsets

Abstract: The pathways leading to the development of different dendritic cell (DC) subsets have long been unclear. In recent years, a number of precursors on the route to DC development, both under steady state and inflammatory conditions, have been described, and the nature of these pathways is becoming clearer. In addition, the development of various knockout mouse models and an in vitro system modelling DC development have revealed the role of numerous cytokines and transcription factors that influence DC development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…GM-CSF is produced at nearly undetectable levels during homeostasis and acts via the GM-CSF receptor, which stimulates the JAK-STAT, MAPK, PI3K and NF-κB pathways (van de Laar et al, 2012). Analyses of mice lacking these cytokines or their receptors revealed that the Flt3L-driven pathway of DC development has the more pronounced effect on DC development during homeostasis in vivo , although M-CSF and GM-CSF also contribute to development of particular subsets of tissue DCs in the steady state (Merad and Manz, 2009; Helft et al, 2010; Sathe and Wu, 2011). As described below, estradiol/ERα signaling regulates both GM-CSF- and Flt3L-mediated DC differentiation from hematopoietic progenitors of myeloid cells.…”
Section: Overview Of DC Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…GM-CSF is produced at nearly undetectable levels during homeostasis and acts via the GM-CSF receptor, which stimulates the JAK-STAT, MAPK, PI3K and NF-κB pathways (van de Laar et al, 2012). Analyses of mice lacking these cytokines or their receptors revealed that the Flt3L-driven pathway of DC development has the more pronounced effect on DC development during homeostasis in vivo , although M-CSF and GM-CSF also contribute to development of particular subsets of tissue DCs in the steady state (Merad and Manz, 2009; Helft et al, 2010; Sathe and Wu, 2011). As described below, estradiol/ERα signaling regulates both GM-CSF- and Flt3L-mediated DC differentiation from hematopoietic progenitors of myeloid cells.…”
Section: Overview Of DC Developmentmentioning
confidence: 99%
“…1) (Merad and Manz, 2009; Sathe and Wu, 2011). Hematopoietic progenitors are contained within a bone marrow population of lineage marker negative (Lin − ) cells that lack surface proteins expressed by mature myeloid, lymphoid or erythroid cells.…”
Section: Overview Of DC Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…IRF-8, Btf3 and Id2 are critical for differentiation of CD8 + cDCs and certain CD103 + tissue DCs (Aliberti et al, 2003;Edelson et al, 2010;Jackson, 2011;Sathe and Wu, 2011), while IRF-4 on the other hand, is critical for differentiation of CD8 -cDC (Geissmann et al, 2010). PU.1 also exhibits differential effect on Fl3t-L-induced or GM-CSF induced DC differentiation (Carotta et al, 2010).…”
Section: Regulation Of Functional Specialization Of DC Subsetsmentioning
confidence: 99%
“…After being connected with immune stimulants, DCs take up and process antigens in peripheral tissues and then migrate to secondary lymphoid organs, where they activate naive T cells. The maturation process of DCs is a multi-step process, including a decrease of the endocytic ability, high cell surface expression of con-stimulatory (CD40, CD80 and CD86) and major histocompatibility complex (MHC) class II molecules, and cytokine induction, especially TNF-α, IL-12 and IL-10 [2, 3]. The common DCs maturation inducers include lipopolysaccharides (LPS), CpGoligonucleotide (CpG ODN), tumor necrosis factor (TNFα), type I interferon (IFN-γ), immune complex and endogenous ligand [4].…”
Section: Introductionmentioning
confidence: 99%